1972
DOI: 10.1139/v72-263
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Co2+ by Oxides from Aqueous Solution

Abstract: The adsorption of Co(II) by Fe3O4, Al2O3, and MnO2 has been studied as a function of Co(II) concentration, solution-pH, and temperature. It is observed that the adsorption of cobalt increases markedly with the solution pH between pH 5 and 7.5. Above pH 8 adsorption becomes increasingly masked by precipitation of Co(OH)2 and no resolution of these two contributions to the loss of Co(II) from solution is possible. A log θ/(1–θ) vs. pH plot is found to be linear between pH 5 and 7.5, where θ is the fraction of oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
5

Year Published

1978
1978
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(64 citation statements)
references
References 7 publications
4
55
0
5
Order By: Relevance
“…They suggested a change from a dominantly aquo surface complex to a more hydroxide-like complex but one that is not identical to the solid hydroxide phase most likely to precipitate. Other XPS studies of Co(II) complexes on ~'-A1203 suggest a correlation between hydrolysis, adsorption, and the formation of aquo-type complexes at low pH and possible formation of a surface precipitate at high pH (Tewari et al, 1972;Tewari and Lee, 1975;Tewari and McIntyre, 1975). Cobalt and Ni sorption on hectorite and montmorillonite studied by XPS (Davison et al, 1991) supported previous results indicating the formation of a hydroxidelike species at high pH and no change in the binding energies of the sorbed species after successive washings, implying strong bonding of the cation to the surface.…”
Section: Spectroscopic Studies Of Sorbed Metal Ionsmentioning
confidence: 94%
“…They suggested a change from a dominantly aquo surface complex to a more hydroxide-like complex but one that is not identical to the solid hydroxide phase most likely to precipitate. Other XPS studies of Co(II) complexes on ~'-A1203 suggest a correlation between hydrolysis, adsorption, and the formation of aquo-type complexes at low pH and possible formation of a surface precipitate at high pH (Tewari et al, 1972;Tewari and Lee, 1975;Tewari and McIntyre, 1975). Cobalt and Ni sorption on hectorite and montmorillonite studied by XPS (Davison et al, 1991) supported previous results indicating the formation of a hydroxidelike species at high pH and no change in the binding energies of the sorbed species after successive washings, implying strong bonding of the cation to the surface.…”
Section: Spectroscopic Studies Of Sorbed Metal Ionsmentioning
confidence: 94%
“…al., 1991) and potentiometric titration (Parfitt et. al., 1983 andTewari, 1981). Both the methods provide the accurate values of pH zpc .…”
Section: Determination Of Zero Point Chargementioning
confidence: 97%
“…However quantification of the biosorption of Co 2+ ions is complicated by the fact that cobalt precipitates at pH higher than 8 and therefore it becomes difficult to distinguish between sorption and precipitation beyond pH 8. Based on the known hydrolysis constant it has been shown that up to pH 8, Co(II) exists mainly as non-hydrolyzed Co 2+ ion but at pH 10 [Co(OH)] + predominates (Tewari 1972;Khan 2003). Moreover, extreme pH values can damage the structure of the (bio)sorbent and therefore decrease metal uptake (Kuyucak & Volesky 1989).…”
Section: Effect Of Ph On Comentioning
confidence: 99%